Personality traits and self-esteem in combat and team sports - Bojanic, Z.; Nedeljkovic, J.; Sakan, D.; Mitic, P. M.; Milovanovic, I.; Drid, P. (Frontiers in Psychology, 2019)
The aim of this research was to examine whether psychological variables which make up basic dimensions of personality and self-esteem distinguish competitors in combat sports from competitors in team sports. The research included 149 respondents, aged 19 to 27 years. The Self-Esteem Scale questionnaire was used to measure self-esteem. The BFI inventory was used to measure personality traits according to the Big Five model: Extraversion, Neuroticism, Conscientiousness, Agreeableness, and Openness to Experience. The basic research question is - does the set of psychological variables which make up basic dimensions of personality and self-esteem statistically significantly distinguish competitors in combat sports from the competitors in team sports? Both mean differences and simple discriminant function analyses for competitors in combat/team sports revealed that self-esteem, neuroticism, and conscientiousness were the most important factors distinguishing the two groups. Practical implications, limitations, and future research directions were discussed